Charlie Hebdo's controversial cartoons in question: stances, translational narratives and identity construction from a cross-linguistic perspective. Issue 5 (20th October 2019) - Constantinou, Maria
ABSTRACT: Charlie Hebdo, a synonym for the universal cause of liberty and freedom of the Press, gained international attention after the terrorist attack of January 2015. However, Charlie Hebdo through its particular humour, which is both culture-bound and ideology-oriented, triggered anger and indignation, mainly after the publication of cartoons portraying little Aylan, the symbol of refugees' tragedy, and in particular, the one which depicted him as "an ass groper". This article sets out to investigate from a cross-linguistic and cross-cultural viewpoint reactions that the most controversial cartoon triggered, while considering both the socio-political context of the event and examining the crisscrossing and competing narratives it gave rise to. In doing so, the study draws heavily on the narrative theory of translation [Baker, Mona. 2006. Translation and Conflict: A Narrative Account . London: Routledge, Baker, Mona. 2007. "Reframing Conflict in Translation." Social Semiotics 17 (2): 151–169, Baker, Mona. 2010. "Narratives of Terrorism and Security: 'Accurate' Translations, Suspicious Frames'." Critical Studies on Terrorism 3 (3): 347–364] and uses concepts and methods from Critical Discourse Analysis, and semiotic approaches to cartoon translation. Working with a trilingual corpus composed of articles from various French, English and Greek online newspapers and blogs, it first delineates the theoretical framework, the methodological approach applied and then it proceeds with the analysis of stancetaking as deployed in headlines and examines from a contrastive viewpoint the competing translational narratives in English and Greek data.